Cryo‐surgery for symptomatic extra‐abdominal desmoids. A proof of concept study. Issue 4 (27th May 2021) - Efrima, Ben; Ovadia, Joshua; Drukman, Ido; Khoury, Amal; Rath, Ehud; Dadia, Solomon; Gortzak, Yair; Albagli, Assaf; Sternheim, Amir; Segal, Ortal
Abstract: Background and Objective: Extra abdominal desmoid tumors are rare, highly aggressive, and invasive benign soft tissue tumors. Current treatment modalities show high levels of recurrence and comorbidities. Cryo‐surgery as an alternative was subsequently investigated. Methods: In this retrospective, single center study 11 patients showing symptomatic tumors were treated with individualized cryo‐surgery. Treatment protocol included preoperative planning using computer rendered 3D models, intraoperative navigation and execution using cone beam guidance, and postoperative magnetic resonance imaging image analysis using a gaussian mixture model software. Subjective outcomes were reported using Short Form Health Survey (SF‐36) questionnaires. Results: Sixteen ablations were performed, each demonstrating a complete match with the determined preoperative plan and model. A total of 9/11 (82%) of patients showed improvements in symptoms and a reduction in tumor volume while 2/11 (18%) did not. Average reduction in tumor volume and viable segments were 36.7% ( p  = 0.0397) and 63.3% ( p  = 0.0477), respectively. Mild complications according to the SIR Adverse Event Classification Guidelines were experienced in 3/16 (19%) ablations. SF‐36 scores showed a statistically significant improvement ( p  = 0.0194) in the mental health category and a nonsignificant ( p  = 0.8071) improvement in the physical health category. Conclusion: Cryo‐surgery using the three‐phase protocol as described may improve the overall outcome of future ablation procedures.